Autonomy, capacity and vulnerable adults: filling the gaps in the Mental Capacity Act. (December 2015) - Herring, Jonathan; Wall, Jesse
Abstract: This paper explores the distinction between being autonomous and having capacity for the purposes of the Mental Capacity Act. These include where a person misuses affective attitudes in making the decision; where a person's decision is not authentic to their values; and where the Mental Capacity Act prevents use of the context or outcome of the decision in assessing capacity. These gaps mean that a person can be found to have capacity, even though they are not properly autonomous. This, we argue, justifies the courts' use of the inherent jurisdiction to protect vulnerable adults who, while having capacity are not able to act autonomously.